Iridescence the Powerful Impact of Accreditation to Osias Colleges, Inc. - Salagan, Aurea C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study investigates the transformative effects of accreditation on an educational institution, focusing on various areas including philosophy and objectives, faculty, curriculum, laboratory facilities, research, library services, student services, social orientation, community involvement, physical plant, and administration. Utilizing a phenomenological historical research design, the research examines the institution's status before and after its voluntary accreditation by PACUCOA, highlighting significant changes such as the alignment of the Vision, Mission, Goals, and Objectives (VMGO) with academic programs, enhanced faculty engagement in research, and improved infrastructure, including the establishment of a new six-story building. The findings reveal that accreditation not only facilitated substantial improvements in institutional quality and student services but also fostered a culture of continuous growth and development, ultimately positioning the institution as a more competitive and respected educational provider in the region.